Improving the motor adaptation of students with special needs to the conditions of inclusive education; 4rd International Multidisciplinary Scientific Conference on Social Sciences and Arts (SGEM 2017); Т. 3: Science & Society. Sociology and healthcare - Davletjyarova K. V. Kseniya Valentinovna (2017, 2017)
Title screen